Alas de ladrillo - Fuentes-Castillo-Warden (2004)
Casa Angelelli-Amato en el Club de Campo Boca Ratón en Pilar, Buenos Aires. Año 2001-2003.
Keywords: FUENTES, OSCAR; CASTILLO, PAZ; WARDEN, MARIANA; BUENOS AIRES; ARGENTINA; VIVIENDAS UNIFAMILIARES; VIVIENDAS SUBURBANAS; COUNTRY CLUBS; CONSTRUCCION; LADRILLO